APLIKASI GAS HHO PADA SEPEDA MOTOR INJEKSI DENGAN MODIFIKASI ECU AFTERMARKET (TIMING PENGAPIAN) - Indah Puspitasari; Noorsakti Wahyudi; Kuntang Winangun; Fadil Noor Rofiq (Jurnal Rekayasa Mesin, 2022)
HHO gas is a gas produced from electrolysis, which is the decomposition of an electrolyte using an electric current which produces Hydrogen Gas and Oxygen Gas / Hydrogen Hydrogen Oxygen. The purpose of this study was to determine the application of HHO gas by increasing ignition timing by 3º, 6º, and 9º using an aftermarket ECU on engine performance and injection motor emissions. The method used in this study is an experiment, testing using a dinotest measuring instrument and a gas analyzer. The results obtained are the highest average power value in all tests obtained on the variable use of HHO Gas without variations in ignition timing using an aftermarket ECU of 5.90 HP at 3500 Rpm engine speed, an increase of 0.13% from the conditions of HHO Gas usage and forward time. . ignition of 3º and 6º, an increase of 0.27% from HHO gas usage conditions and a forward ignition time of 9º. Then the highest average torque value from all tests was obtained on the variable using HHO Gas and variations in ignition timing using an aftermarket ECU with an advance of 3º of 14.39 Nm at 3000 rpm engine speed, an increase of 0.29% from conditions using HHO Gas without using Variation ignition timing using aftermarket ECU.